Performance Capability Analysis and Regional Budget Evaluation in Implementing Regional Autonomy in Dharmasraya District - Septria, Doni; Heryanto, Heryanto (Archives of Business Research, 2019)
This study tries to find out the Performance Capability Analysis and Evaluation of Regional Budget in Running Regional Autonomy in Dharmasraya Regency. The research population is the financial report of the Regional Government of Dharmasraya Regency since the establishment of this district in 2004 by taking samples of financial statements for the past 4 years. This study uses the method of financial ratio analysis. The results of the study show that the district financial independence ratio Dharmasraya is in the instructive criteria, meaning that regional financial independence is still very low because this role is more dominant than the independence of local governments. The degree of fiscal decentralization is in the very poor category, where the average is less than 10%, which is 7.92%, which means that Dharmasraya District’s Original Revenue in financing its own development is only 7.29% of the total Regional Revenue during the 2014-2017 period The effectiveness of the PAD ratio is in the effective criteria, meaning that the ability of the Dharmasraya Government to realize PAD revenues is an average of 86% of the targeted PAD. The activity ratio shows that the Dharmasraya District Government uses more funds for apparatus shopping activities than public spending. The shopping harmony ratio shows that the Dharmasraya District Government uses more funds for indirect shopping activities compared to direct shopping. The empirical findings indicate that for the performance of the Regional Secretariat staff in the Dharmasraya Regency, the Regional Secretariat of the Dharmasraya Regency needs to pay attention and focus more on improving the Competency and Workload factors.